3D Polygon Mesh Encryption Based on 3D Lorenz Chaotic Map - Alsalam Ali, Nashwan; S. Rahma, Abdul Monem; H. Shaker, Shaimaa (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The multimedia application developments in recent years lead to the widespread of 3D model applications. It becomes more popular in various fields as well as exchanging it over the internet. The security of the 3D models is a very important issue now a day, so the scheme for encrypting the 3D model will be proposed in this work. In this proposed scheme, the 3D polygon mesh model will be protected through the encrypting process based on a 3D Lorenz Chaotic map where the vertices value of the 3D polygon mesh model will be modified using 3D keys generated by 3D Lorenz Chaotic Map, which has excellent property and provides a good diffusion. The proposed scheme was implemented on various 3D models, which have a different number of vertices and faces. The experimental results show that the proposed scheme has good encryption results, which were noted through completely deforming and changing the whole shape of the 3D models. The Hausdorff Distance (HD) and histogram metrics are adopted to calculate the matching degree between the original and extracted model. The results show that the original and extracted model are identical through the values of HD, where they are approximately zero, and the histogram visually is identical.